Cold hydraulic condensation (sealer-based) root canal obturation: what are the differences in clinical techniques from the traditional obturation? - Banomyong, Danuchit (Thai Endodontic Journal, 2025)
Recently, a calcium silicate-based root canal (CSRC) sealer has been introduced. CSRC sealer is designed for a special obturation technique by using it as a main obturation material in root canals, namely cold hydraulic condensation (CHC) or sealer-based root canal obturation. The obturation techniques of CHC using CSRC sealer are different from that of traditional obturation. In particular, more conservative root canal preparation, single matched main cone, final rinse with normal saline solution or distilled water, moist canals before obturation, creating gutta-percha plug at the orifice, cleaning the sealer using sponge or micro-brush followed by irrigation, and delaying post-space preparation are described.